Preparation and Performance Study of Alkali-active Gypsum Mixture System - Gou, Mifeng; Yang, Xiangquan; Zhang, Mengdan (International Journal of Mechanical and Electrical Engineering, 2024)
To improve the mechanical properties and water resistance of gypsum specimens, thus solving the pollution problem due to the accumulation of flue gas desulfurization gypsum (FGD gypsum), etc. The article utilizes flue gas desulfurization gypsum, gypsum citrate, and mineral powder as the main raw materials under a fixed ratio. The Alkali-activation gypsum-based cementitious material (Alkali-activation GM-S95 system) was obtained by modifying it with 0-5% Na(OH) and Ca(OH)2 alkaline admixtures, and the mechanical properties and water resistance of the Alkali-activation GM-S95 system were thoroughly investigated. The structural characteristics of the Alkali-activation GM-S95 system specimens were investigated using XRD, TG, SEM and LF-NMR techniques to explore their interactions. The results showed that the compressive strength of the Alkali-activation GM-S95 system was significantly increased to 26 MPa when 4% Ca(OH)2 was added alone, and the water absorption was decreased to 12.5%.The addition of 4% Ca(OH)2 caused the crystals of gypsum dihydrate to be thicker and denser, and AFT and C-S-H gels were produced, which were attached around the crystals of gypsum dihydrate. The addition of different admixtures can reduce the proportion of large pores and further fill the crystal structure. In summary, the addition of 4% Ca(OH)2 can improve the compressive strength and water resistance of the samples of Alkali-activation GM-S95 system, thus laying a solid foundation for the comprehensive utilization of flue gas desulfurization gypsum.